EFEKTIFITAS TILANG ELEKTRONIK (E-TILANG) BAGI PELANGGAR BERKENDARAAN BERMOTOR DI WILAYAH HUKUM POLDA BALI - Juliana, I Made Krisna; Hengki, I Gusti Bagus (Jurnal Hukum Mahasiswa, 2024)
The application of E-Tilang is an effective option in implementing tickets for traffic violators so that it can be a solution when enforcement takes place. This research aims to determine the effectiveness of the implementation of e-ticketing as well as the supporting factors and obstacles in implementing e-ticketing in the jurisdiction of the Bali Regional Police. The type of research used is empirical legal research and uses data analysis methods, namely qualitative analysis. Based on the research results, the effectiveness of e-ticket implementation in society can be studied through the theory of law enforcement effectiveness. The supporting factors in implementing E-Tilang include the connectivity of the E-Tilang system which is able to connect with other systems or internet providers so that many traffic violations are detected. Meanwhile, the obstacle factors are the lack of facilities and equipment as well as law enforcement factors.